The effect of dietary and exercise modification program for obesity prevention among primary schools in Nakhon Ratchasima municipality - สุวรรณอำภา ณภัทร; สละวงษ์ลักษณ์ ทองทิพย์ (Ratchaphruek Journal, 2019)
This quasi-experimental research was to study the effect of dietary and exercise modification program for obesity prevention. The samples were 60 students at primary schools who were divided into two groups equally, one was an experimental group, and the other was a control group. Research instruments were the instruments were self-administrated questionnaire including, questionnaire about knowledge, self-evaluation formeducation, and observation checklist. This program took 40 hours-12 weeks. Data analyses were frequency, percentage, means, standard deviation, paired sample t-test and independent t-test. The results were found that the mean scores after the experiment were higher than before the experiment of the experimental group and the control group in terms of knowledge, perception of self-efficacy, outcomes expectations and practice of dietary and exercise at .05 levels significantly.